2007
DOI: 10.1007/s00200-007-0043-z
|View full text |Cite
|
Sign up to set email alerts
|

Skew-cyclic codes

Abstract: International audienceWe generalize the notion of cyclic codes by using generator polynomials in (non commutative) skew polynomial rings. Since skew polynomial rings are left and right euclidean, the obtained codes share most properties of cyclic codes. Since there are much more skew-cyclic codes, this new class of codes allows to systematically search for codes with good properties. We give many examples of codes which improve the previously best known linear codes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
167
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(170 citation statements)
references
References 3 publications
2
167
0
1
Order By: Relevance
“…It is shown in [2,3] that under the usual identification of vectors with polynomials, the skew cyclic shift (the second condition in the definition above) corresponds to skew multiplication by x in F [x; θ], and skew cyclic codes are ideals in F [x; θ]/(x n − 1) when m|n.…”
Section: Ifmentioning
confidence: 99%
See 3 more Smart Citations
“…It is shown in [2,3] that under the usual identification of vectors with polynomials, the skew cyclic shift (the second condition in the definition above) corresponds to skew multiplication by x in F [x; θ], and skew cyclic codes are ideals in F [x; θ]/(x n − 1) when m|n.…”
Section: Ifmentioning
confidence: 99%
“…Boucher, W. Geiselmann and F. Ulmer in [2], and in [3], took another direction when they studied a more generalized class of linear and cyclic codes using a non-commutative ring. They studied what they called skew cyclic codes, where the generator polynomial of a skew cyclic code comes from a non-commutative ring F [x; θ], where F is a finite field and θ is a field automorphism of F .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [8], Hammons et al showed that some important binary nonlinear codes can be obtained from cyclic codes over Z 4 through the Gray map. Recently, in [2], D. Boucher et al introduced the class of θ-cyclic (skew cyclic) codes that generalizes the concept of cyclic codes over non-commutative polynomial rings, called a skew polynomial ring, to construct these types of codes.…”
Section: Introductionmentioning
confidence: 99%